The Effect of the Addition of Green Tea Extract on the Stability of Sappan Extract Due to Ultraviolet Radiation - Tarumiyo, Aureli Amaliyah; Dewi, Kurnia Harlina; Asben, Alfi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aimed to evaluate the effect of green tea extract addition on the stability of Caesalpinia sappan (sappanwood) extract under ultraviolet (UV) radiation exposure. A completely randomized factorial design was employed using two factors: the combination ratio of sappanwood and green tea extract (100%:0%, 85%:15%, and 70%:30%) and the duration of UV exposure (0, 30, and 60 minutes). Parameters analysed included colour, antioxidant activity (IC??), total anthocyanin content, and spectrophotometric absorbance. The results demonstrated that both factors significantly affected the stability of the extract. The addition of green tea extract, particularly at a ratio of 85% sappanwood to 15% green tea, yielded the highest antioxidant activity (6.77 ?g/mL) and anthocyanin total (4.98%), indicating enhanced stability due to the antioxidant and photoprotective effects of catechins. However, the longer the exposure time, the lower the antioxidant activity and total anthocyanin. These findings emphasize the possible use of green tea as a natural copigment to enhance the photostability of brazilin-containing herbal extracts, thereby broadening their functional and pharmaceutical applications. Contribution to Sustainable Development Goals (SDGs):SDG 9 : Industry, Innovation, and InfrastructureSDG 13: Climate ActionSDG 15: Life on Land